2015
DOI: 10.1590/1807-1929/agriambi.v19n10p931-938
|View full text |Cite
|
Sign up to set email alerts
|

Características morfofisiológicas e produtividade da palma forrageira em diferentes lâminas de irrigação

Abstract: R E S U M OMuitas são as suposições quanto à baixa exigência de água da palma mas tais informações dependem de estudos de análise do desempenho da cultura a diferentes condições hídricas. Assim, objetivou-se verificar o efeito de diferentes lâminas de irrigação sobre a morfofisiologia e desempenho produtivo da palma forrageira cultivada em ambiente Semiárido. O experimento foi conduzido no segundo ano produtivo da cultura, em Serra Talhada, PE. As lâminas de água aplicadas totalizaram, ao final do ciclo, 976, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
5
45

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 11 publications
2
40
5
45
Order By: Relevance
“…In this case, spineless cactus produces well in areas with annual precipitation of up to 750 mm [14]. These results lead to the understanding that the productive beneits of increased of water blade for spineless cactus are more apparent in regions with very low rainfall levels compared to regions where the rainfall values exceed 750 mm [67,68].…”
Section: Irrigated Soilmentioning
confidence: 93%
See 2 more Smart Citations
“…In this case, spineless cactus produces well in areas with annual precipitation of up to 750 mm [14]. These results lead to the understanding that the productive beneits of increased of water blade for spineless cactus are more apparent in regions with very low rainfall levels compared to regions where the rainfall values exceed 750 mm [67,68].…”
Section: Irrigated Soilmentioning
confidence: 93%
“…Indeed, Queiroz et al [67] evaluated the efect of application of diferent irrigation blades (976, 1048, 1096, 1152 and 1202 mm) on the productive performance of spineless cactus cultivated in semiarid environment and check that there were no diferences in number of cladodes and in fresh and dry annual biomass between treatments, revealing that the increase of irrigation has not contributed to increase the yield of crop. Flores-Hernández et al [68] also found that supplemental irrigation (740, 1060 and 1380 mm) did not provide increments cladodes production and dry mater productivity.…”
Section: Irrigated Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Felker and Inglese (2003) mention that sites with high atmospheric demand and rainfall below 350 mm year -1 , the use of irrigation is essential to ensure a good yield. Queiroz et al (2015) report a productive increase of forage cactus up to water depths of 1048 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Evapotranspiration (ET) varies among species, as well as with phenology, as a result of changes in resistance to the transpiration process, height, leaf area, among other factors related to plant morphology (Lemos Filho et al, 2010). At the same time, ET is affected by crop management and soil water availability, which induces morphophysiological variations in the plant, reflecting in its growth rate (Kiremit & Arslan, 2016;Kresoviae et al, 2016;Queiroz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%